Dry matter in fruits, leaves and plagiotropic branches of grown coffee trees in the western amazon - Dubberstein, Danielly; Partelli, Fabio Luiz; Schmidt, Raquel; Dias, Jairo Rafael Machado; Covre, André Manzoli (Coffee Science - ISSN 1984-3909, 2017)
Different factors may influence the accumulation of dry matter in the coffee, as the nutritional management and the phenological stage of the plant. This study aimed to assess the number of fruits and the dry matter content in fruits, leaves and reproductive branches of Coffea canephora, fertilized and unfertilized conditions in the Western Amazon. The experiment was conducted in clonal tillage with randomized complete blocks in time a split plot arrangement. The main plots were constituted of two managements of fertilizer and subplots accommodated the evaluation times. Collections of branches were made from the developmental stage of very small berries to maturity. The number of fruits per branch, total dry matter of fruits per branch, dry matter per fruit, leaves dry matter and dry matter plagiotrophycal were evaluated. In the experimental conditions mineral fertilization did not differ from the number of fruits and dry matter content of organs. The dry matter accumulation curve in the fruit adjusted to sigmoidal model and there was an evident increase from the 56th day of flowering, after the significant drop phase very small berries. In reproductive branches was linear increase in dry matter content during the reproductive phase, unlike the leaves, in which there was a decrease of dry matter.